Penerapan Metode AHP Dan Promethee Pada Sistem Pendukung Keputusan Dalam Pemilihan Investasi Saham Tembakau - Muhammad Hilmi Fauzi; Riffa Haviani Laluma (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In the era of digital 4.0, the ease of stock investment is a crucial decision that influences the wealth growth of individuals and companies. In the complex stock market environment, it is important for investors to have effective tools to aid in making better investment decisions. Decision Support System (DSS) using the Analytic Hierarchy Process (AHP) and Promethee (Preference Ranking Organization Method for Enrichment Evaluations) methods can provide valuable guidance in stock investment selection. This research aims to develop a decision support system that incorporates the AHP and PROMETHEE methods in the context of stock investment selection.